Peran Komunitas Seni dan Budaya dalam Pengembangan Desa Mandiri Budaya di Desa Ekowisata Pancoh - Mulyasari, Runavia; Maizida, Karlina; Purwandani, Intan (Gadjah Mada Journal of Tourism Studies, 2023)
Community-based tourism management precariously depends on a robust community, especially in tourist villages. Establishing an organizational framework characterized by effective coordination and well-defined member relationships strengthens the community and defines each individual's role and responsibility. To enhance the efficiency of the established structure, this study aims to investigate the function of the arts and cultural community within Pancoh Ecotourism Village and ascertain its capacity for further development as a Cultural Village. This study utilises a community development framework (Community Development Foundation, 2011) comprising six principles—common goals, cooperation, strengths and independence, equity and inclusiveness, participation, and community empowerment. Community representatives, village officials, tourism actors, and workers of Pancoh Ecotourism Village participated in a series of focus group discussions (FGD). Consequently, the inhabitants of Pancoh Ecotourism Village successfully established an organisational framework that catered to their requirements and unambiguously delineated every individual's specific duties and obligations. In addition, actors, tourism managers, and arts and culture community members can solicit diverse opportunities and curate cultural tour packages that feature renowned artistic and cultural attractions and products.